A literature review: Exploring organizational learning orientation as antecedent of Information Technology (IT) infrastructure capability to achieve organizational agility - Hassan, N.H.B. (2013)
This research-in-progress paper explores how organizational learning orientation can affect Information Technology (IT) infrastructure capability. Four dimensions of organizational learning orientation are analyzed; committed to learning; share vision; open-mindedness; and intra-organizational knowledge sharing. The relationship between IT infrastructure and two types of organizational agility (market capitalizing agility and operational adjustment agility) is also measured. Drawing upon Resource-based view (RBV) and dynamic capabilities theory, six hypotheses are developed to better understand how can organizations can be agile by preparing its IT capability with the right organizational learning orientation. Structural Equation Modeling (SEM) will be employed to analyze whether the collected data support our hypotheses. The propose research model will be empirically validated in the future stages of this research. Â© 2013 IEEE.